Clinical Characteristics and Treatment of Patients with IgA Nephropathy and Hepatitis B Surface Antigen. (May 2013) - Sun, In O; Hong, Yu Ah; Park, Hoon Suk; Choi, Sun Ryoung; Chung, Byung Ha; Park, Cheol Whee; Yang, Chul Woo; Kim, Yong Soo; Choi, Bum Soon
<x xml:space="preserve">Abstract</x> Background: The aim of this study is to investigate the clinical characteristics and our experience of treating patients with IgA nephropathy (IgAN) and IgA nephropathy with hepatitis B surface antigen (HBs-IgAN). Methods: From 1996 to 2011, biopsy-proven IgAN was diagnosed in 477 patients and 22 (4.6%) had hepatitis B surface antigen (HBsAg). Of these, we included 360 patients who had more than 6-month follow-up period, and compared clinical characteristics and renal function decline between the patients with IgAN and HBs-IgAN. Results: Of 360 patients, 22 were classified as HBs-IgAN. There were no differences in the clinical characteristics and renal function decline between idiopathic IgAN and HBs-IgAN (–0.01 vs. –0.17 mL/min per 1.73 m2/month, p = 0.319). Of 22 patients with HBs-IgAN, nine had hepatitis B virus (HBV) replication marker (RM), of which six were treated with anti-viral agents. However, there were no differences in renal function decline and urinary protein excretion between patients who did or did not receive anti-viral therapy. Five patients with HBs-IgAN received corticosteroid therapy. Of these, three without HBV RM and one with HBV RM who received entecavir did not exhibit active viral replication, whereas the other patients with HBV RM experienced viral replication after lamivudine was discontinued. Conclusion: There were no differences in the clinical characteristics and prognosis between the patients with IgAN and HBs-IgAN. Further, there were no differences in renal function decline and urinary protein excretion between patients with and without anti-viral therapy. Anti-viral therapy may be considered for treating patients with HBs-IgAN receiving immunosuppressants according to HBV RM.